Asymmetry of lower limb strength and jumping ability of young soccer players - Rutkowska-Kucharska, A. (Acta of Bioengineering and Biomechanics, 2020)
Purpose: The aim of this study was to evaluate the potential correlation between asymmetry of lower limb muscle torque, asymmetry of vertical ground reaction force during take-off in young soccer players and their jumping abilities. Methods: Twenty-three young soccer player (16.9±0.64 years old) participated in measurements. An isokinetic dynamometer, the Biodex System, was applied to test muscle torque (PT) of the knee flexors and extensors. The vertical ground reaction force (vGRF) was recorded from two Kistler plates. Jumping abilities were assessed with the horizontal (HJ) and vertical jump (VJ) tests. The asymmetry index (AI) was used to assess the asymmetry of the limbs. Results: The asymmetry index showed the highest asymmetry (over 10%) for the PT under static conditions for knee flexors and extensors. The correlation (-0.432, p=0.038) was found between the asymmetry of vGRF and the height of the VJ. There was no correlation between the muscle torque and the height of the vertical jump. However, a correlation between the HJ length and muscle torque for flexors and extensors of the right and left lower limb was found. Conclusions: The asymmetry of the muscle torque of the flexors and extensors of the knee joint does not correlate with the results of both jumping ability tests. There was a statistically significant correlation between the vGRF asymmetry index during take-off and the height of the VJ. In the HJ, such a relationship was not found.